El dilema de los prisioneros y la moral - Carlos Rosenkrantz (Crítica)
In this paper I try to highlight the relationship between self-centered Reasons and morality. My basic aim is to show that not even the most sophisticated attempts of current philosophical literature can bridge the wide gap that detaches from one another. I focus the 'prisoner's dilemma' showing that the best pay-off for everybody in that situation can only be obtained if everybody refuses to think in terms of the maximization of his or her utility and decides to cooperate keeping silent. I argue that this decision cannot be based in self-interested reasons because self-interested people can never generate the expectations needed for cooperation to arise. This impossibility stands as a wall against which Gauthier's and Axelrod's attempts bounce. Which I call in the text the metha-solution (Gauthier) and the iterated solution (Axelrod) cannot overcome the fact that knowing what the rest of as self-interested I would never cooperate because they will try to exploit my cooperation and were they altruistic I would never cooperate either because I will try to exploit their cooperation. Nevertheless there is a limited plausibility in the approaches I challenge which derives from the assumption that some people have already decide to cooperate not on bases of self-interested reasons but on reasons of different sort. Obviously this cannot serve as a proof of the existence of the bridge I referred above. Finally I sketch why there are reasons to be moral which make the decision of restraining my actions to preserve the interests of others a rational one.